The effects of waiting time towards customers’ satisfaction at fast food restaurant in Kuala Terengganu / Aina Nur Nadiah Mohd Nasir and Nur Athirah Muda - Mohd Nasir, Aina Nur Nadiah; Muda, Nur Athirah (2020)
The primary purpose of this study is to examine the various effects of waiting time towards customers’ satisfaction. Researchers surveyed 280 randomly selected customers of the selected five (5) fast food restaurant outlets in Kuala Terengganu during weekends. This study used convenient sampling to acquire the potential respondents. Besides, the study have been identified physical factor (ambient and design and facilities), social factor (restaurant employee and perceived crowding) are the factors that contribute to waiting time at fast food restaurant in Kuala Terengganu. Moreover, physical factor (design & facilities) is the dominant factor of waiting time at the fast food restaurant. In addition, the physical factor (design) and social factor (perceived crowding) are the variables that give significant predators. It is hope that this study may offer some better understanding on the effects of waiting time towards customer satisfaction in the fast food establishments.